Design Billing Architecture for Formwork Materials in Construction Industry - et. al., Bholanath Mukhopadhyay, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Inventory management is one of the major problems faced by various companies. Traditional ways of billing method have various disadvantages as they were done manually therefore there were lots of chances of errors in the transaction. The error in the payment and transaction leads to the breakdown of the customer's trust and Customer Behavior Relation gets affected. The pen-paper billing techniques were time-consuming and uncomfortable for the business and can lead to various kinds of error. The development of an Inventory management system reduces the manual task and increases the automation works which results in less error and increased customer satisfaction. The billing architecture of our Inventory management system helps in building customer relationship behaviour and provides a way to grow the business. The payment, transaction and transaction history can be easily visible to the customers.